2018
DOI: 10.1519/jsc.0000000000001906
|View full text |Cite
|
Sign up to set email alerts
|

Higher Quadriceps Roller Massage Forces Do Not Amplify Range-of-Motion Increases nor Impair Strength and Jump Performance

Abstract: Roller massage (RM) has been reported to increase range-of-motion (ROM) without subsequent performance decrements. However, the effects of different rolling forces have not been examined. The purpose of this study was to compare the effects of sham (RMsham), moderate (RMmod) and high (RMhigh) RM forces, calculated relative to the individuals' pain perception, on ROM, strength and jump parameters. Sixteen healthy individuals (27 ± 4 years) participated in this study. The intervention involved three 60-second qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 27 publications
3
48
0
1
Order By: Relevance
“…Moreover, the efforts required by the participant in order to achieve greater pressures in each condition cannot be discounted, as foam rolling may be more passive than roller massage, in which the pressure is directly proportional to the force output of the participant. At present, the effects of pressure and effort alone, in addition to their interaction, in improving ROM, to the authors' knowledge, have yet to be fully elucidated; however, recent work by Gabrow et al 29 suggests that pressure differences result in more pain, but do not have implications for yielding differential active and passive ROM outcomes. Therefore, despite the fact that interventions in the present study likely resulted in different pressures, this should not have influenced the results.…”
Section: Resultsmentioning
confidence: 92%
“…Moreover, the efforts required by the participant in order to achieve greater pressures in each condition cannot be discounted, as foam rolling may be more passive than roller massage, in which the pressure is directly proportional to the force output of the participant. At present, the effects of pressure and effort alone, in addition to their interaction, in improving ROM, to the authors' knowledge, have yet to be fully elucidated; however, recent work by Gabrow et al 29 suggests that pressure differences result in more pain, but do not have implications for yielding differential active and passive ROM outcomes. Therefore, despite the fact that interventions in the present study likely resulted in different pressures, this should not have influenced the results.…”
Section: Resultsmentioning
confidence: 92%
“…However, they did note that the amount of pressure that is required to induce an increase in ROM is unknown [36]. Grabow et al reported no differences in active ROM between differing relative loads (15, 21 and 27% of body mass) [37]. There was however, a significant increase in ROM for all loads immediately and 10 min following the foam rolling (7 and 6.9%, respectively), despite an increase in the rating of perceived pain.…”
Section: Range Of Movementmentioning
confidence: 97%
“…A number of studies have revealed conflicting results relating to SMR and jump performance [7,23,37,[41][42][43][44].…”
Section: Neuromuscular Performancementioning
confidence: 99%
“…The existing body of research provides several hypotheses regarding how the body responds to RM interventions. Researchers believe the direct myofascial compression of RM devices may produce a local mechanical and global neurophysiological response that influences tissue relaxation and pain in the local and surrounding tissues through afferent central nervous system (CNS) pathways (Aboodarda et al, 2015;Grabow et al, 2018). For the mechanical effect, the direct roller compression may change the viscoelastic properties of the local myofascia by mechanisms such as reducing myofascial restriction, fluid changes, and cellular responses (Kelly and Beardsley, 2016).…”
Section: Mb1 Ball Versus Mbx Ball (Video)mentioning
confidence: 99%
“…C-tactile fibers) (Aboodarda et al, 2015), mechanoreceptors (Young et al, 2018), afferent central nociceptive pathways (gate theory of pain) (Cavanaugh et al, 2017), and descending anti-nociceptive pathways (diffuse noxious inhibitory control) (Aboodarda et al, 2015). These postulated responses are often seen clinically by posttest changes in joint ROM and pain perception which lends evidence to the sensitivity of the myofascia to external forces (Grabow et al, 2018).…”
Section: Mb1 Ball Versus Mbx Ball (Video)mentioning
confidence: 99%